Español: Español - Pfleger, Sabine (Facultad de Ciencias Políticas y Sociales, 2021)
With the arrival of the feminist movement "ni una menos" in Mexico, a change can be perceived in the way women take over public spaces as well as symbolic-discursive spaces. In this contribution I analyze some of the recurring discursive patterns that build a more agentive feminist identity in Mexico, focusing on the linguistic-semantic part of the slogans and statements of graffiti, banners and posters carried by the members in two massive concentrations on August 12 and 16, 2019 in Mexico City, as well as the massive protest on March 8, 2020 and the national strike "a day without us" on March 9, 2020. Using two fundamental semantic principles, the semantic condensation of enculturated concepts and force dynamics I detect four recurring discursive-symbolic patterns that point to a new agency in the construction of the identity within the feminist movement in Mexico in the course of the last two years.